From Competition to Concentration: Theoretical Evolution of Market Power through Monopoly and Monopsony - Fatmawati, Fatmawati; Nurbayani, Sri Undai; Alisyahbana, Andi Naila Quin Azsisah; Isma, Andika; Muflih, Betania Kartika (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study explores the theoretical evolution of market power from classical competition toward concentrated market structures, emphasizing the dual manifestations of monopoly and monopsony. Using a systematic literature review of foundational and contemporary sources, the research traces how microeconomic theory has transitioned from equilibrium-based efficiency models to dynamic analyses of strategic behavior, information asymmetry, and digital dominance. The findings reveal that monopoly and monopsony are symmetric mechanisms of price distortion—each reducing welfare through the restriction of mutually beneficial exchanges. Monopolies elevate prices by controlling output, while monopsonies depress input prices by restricting demand, resulting in comparable deadweight losses and efficiency reductions. Empirical evidence shows that rising market concentration, particularly in digital industries, has deepened income inequality and diminished labor’s share of output. Digital platforms exemplify the convergence of monopoly and monopsony power, leveraging data analytics, algorithms, and network effects to dominate both product and labor markets. These dynamics extend traditional theories of market power beyond static frameworks, emphasizing their systemic and global nature. The study concludes that contemporary market power demands an integrated analytical and policy approach. Effective regulation must simultaneously address consumer welfare, labor market fairness, and innovation incentives. By synthesizing insights from industrial organization, welfare economics, and digital competition studies, this paper contributes to a refined understanding of how monopoly and monopsony shape economic outcomes in the twenty-first century. The results highlight the need for adaptive competition policies to preserve efficiency and equity in a data-driven global economy.